Implementation of Angklung Extracurricular Activities in Supporting Memory Development of Children Aged 5–6 Years - Rahmi, Rizky Renika; Sundari, Rista (PIAUD Universitas Islam Negeri Sunan Kudus, 2025)
This study aims to describe the implementation of angklung extracurricular activities and explore their role in supporting the memory development of children aged 5–6 years at Himawari Kindergarten. A descriptive qualitative approach was employed, involving 18 children from Group B, along with teachers and the school principal as participants. Data were collected through observations, interviews, and documentation, and analyzed using the Miles and Huberman interactive model. The findings indicate that angklung activities provide meaningful learning experiences that support children’s memory development, as reflected in their ability to recall tones, rhythmic patterns, and teacher instructions during practice sessions. The activity implementation consisted of three main stages: preparation, core practice, and closing, utilizing learning strategies such as demonstration, repetition, and musical games. Several challenges emerged, including differences in children’s abilities, limited equipment, and fluctuations in focus; however, these were addressed through adaptive and engaging teaching approaches. Overall, angklung extracurricular activities contribute not only to the development of auditory and motor memory but also to the enhancement of children’s discipline, cooperation, and self-confidence <w:LsdException Lock